It's not all about you : new perspectives on address research - Kluge, Bettina; Moyna, María Irene; Simon, Horst J., 1967-; Warren, Jane, 1958- (Topics in address research, 2019)
"The twenty-first century has seen a surge in cross-linguistic research on forms of address from increasingly diverse and complementary perspectives. The present edited collection is the inaugural volume of Topics in Address Research, a series that aims to reflect that growing interest. The volume includes an overview, followed by seventeen chapters organized in five sections covering new methodological and theoretical approaches, variation and change, address in digital and audiovisual media, nominal address, and self- and third-person reference. This collection includes work on Cameroonian French, Czech, Dutch, English (from the US, UK, Australia, and Canada), Finnish, Italian, Mongolian, Palenquero Creole, Portuguese, Slovak, and Spanish (in its Peninsular and American varieties). By presenting the work in English, the book offers a bridge among researchers in different language families. It will be of interest to pragmatists, sociolinguists, typologists, and anyone focused on the emergence and evolution of this central aspect of verbal communication"--